1977
DOI: 10.1126/science.831268
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Lowering of Self-Stimulation Thresholds: Lack of Tolerance with Long-Term Administration

Abstract: Rats were given increasing amounts of morphine over a period of weeks in order to achieve tolerance. Doses of the drug which initially reduced the threshold for self-stimulation behavior continued to do so after long-term administration. These results demonstrate a persistent central effect of morphine which may be related to the opiate "high."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(40 citation statements)
references
References 10 publications
4
36
0
Order By: Relevance
“…Another possible explanation for the discrepancy in the effects of NPY on LH self-stimulation might be that a different ICSS method was used in the present study than in the studies that reported that NPY does not affect the reinforcing effects of LH self-stimulation (Cabeza de Vaca et al, 1998;Fulton et al, 2002). In the present study a rate-independent discrete-trial method was used to determine the effects of NPY on LH self-stimulation (Esposito and Kornetsky, 1977). In the studies conducted by Fulton, Cabeza de Vaca and colleagues a rate-dependent ICSS method was used to investigate the effects of NPY on LH self-stimulation (Cabeza de Vaca et al, 1998;Fulton et al, 2002).…”
Section: Experiments 6 Effect Of [D-hismentioning
confidence: 69%
“…Another possible explanation for the discrepancy in the effects of NPY on LH self-stimulation might be that a different ICSS method was used in the present study than in the studies that reported that NPY does not affect the reinforcing effects of LH self-stimulation (Cabeza de Vaca et al, 1998;Fulton et al, 2002). In the present study a rate-independent discrete-trial method was used to determine the effects of NPY on LH self-stimulation (Esposito and Kornetsky, 1977). In the studies conducted by Fulton, Cabeza de Vaca and colleagues a rate-dependent ICSS method was used to investigate the effects of NPY on LH self-stimulation (Cabeza de Vaca et al, 1998;Fulton et al, 2002).…”
Section: Experiments 6 Effect Of [D-hismentioning
confidence: 69%
“…Results from subsequent studies using similar procedures showed that, early in their time course, morphine and heroin depressed ICSS, but this initial depression was followed by later facilitation (Adams et al, 1972;Lorens and Mitchell, 1973;Koob et al, 1975). These time-dependent effects in free-operant procedures highlighted the difficulty of dissociating abuse-related from motor effects in free-operant procedures and prompted subsequent studies with discrete-trial procedures in an effort to dissociate abuse-related and sedative effects; these studies found facilitation of ICSS even at early time points (Marcus and Kornetsky, 1974;Esposito and Kornetsky, 1977). More recent studies with frequencyrate procedures have confirmed that mu agonists produce complex effects on ICSS determined by factors that include dose, pretreatment time, and efficacy of the agonist at mu receptors (O 'Neill and Todtenkopf, 2010;Altarifi and Negus, 2011;Altarifi et al, 2012Altarifi et al, , 2013.…”
Section: B Opioidsmentioning
confidence: 99%
“…First, whereas and ␦ opioid receptor agonists tend to elicit conditioned place preferences and opioid agonists conditioned place aversions (Mucha and Herz, 1985;Bals-Kubik et al, 1993), both OFQ/N and Ro 64-6198 seem neutral in tests of place conditioning (Devine et al, 1996;Ciccocioppo et al, 2000;Le Pen et al, 2002). In tests of intracranial self-stimulation, both and ␦ opioid agonists generally lower response threshold (Esposito and Kornetsky, 1977;Jenck et al, 1987), whereas opioid agonists seem to increase threshold (Todtenkopf et al, 2004). On the other hand, Ro 64-6198 seems inert in intracranial self-stimulation threshold experiments (Jenck et al, 2000).…”
Section: Characterization Of Orl-1 Agonist Discriminative Cue 655mentioning
confidence: 99%